The Tana Delta in the Indian Ocean trade network, archaeological evidences of local and global interactions in a Kenyan coastal hinterland - (:unkn) unknown (My University, 2020)
This PhD thesis is interested in reconstituting history of a Kenyan coastal region poorly known: the Tana Delta. G.Abungu and F.Chami showed the importance of deltaic areas in East-Africa as hinterland for coastal urban trade centres. However, we still know little upon the past occupations in these regions. Despite works on the Tana River during the 1980’s, there is a lack of archaeological data about the past inhabitants and the past environment in its deltaic area.My ongoing study proposes to interrogate the potential role of the Tana Delta in the Indian Ocean trade network. Simultaneously, the excavated artefacts could give a chance to understand the Tana Delta for itself, beyond its role of hinterland. Based on the data gathered during the missions 2018 and 2019, I suggest to take the delta as a specific entity with its own economic and social interactions.Considering the fieldwork still in progress, this communication presents an overview of the previous fieldworks results. After a general presentation of the objectives and the current state of research, I will present the main data collected up to now in the Tana Delta, and finish with a specific focus on a previously unknown medieval archaeological site: Sango farm Mtetemo.This site, test excavated twice, gives an insight of an active rural place. Tana Tradition potteries, beads, slags and bones are part of the material found on this site, opening to a succession of questions. The presence of this pottery interrogate the place of Mtetemo into the wide East-African network. The range of unearthed beads associated with ceramic bead- grinders make me hypothesize that Mtetemo was a bead-making place. The unearthed and collected material interrogate the environment of the site found in the vicinity of the Lake Tana Delta in the Indian Ocean trade network Shakababo. Indeed, iron slags and faunal bones (cattle and fish mostly) conduct to question the possibility of a local production for a local netw
Keywords: African Research